Peran Zakat Produktif dalam Pemberdayaan Ekonomi Mustahik - Mafluhah, Mafluhah (Universitas Islam Lamongan, 2024)
Zakat, as one of the pillars of Islam, has an important role in realizing social and economic justice for Muslims. One of the effective zakat distribution schemes in achieving this goal is productive zakat. This study aims to analyze the role of productive zakat in the economic empowerment of mustahik. The research method used is a literature study by reviewing various scientific sources, such as journals, books, and scientific articles. The results of the study indicate that productive zakat has a significant role in the economic empowerment of mustahik through several aspects such as zakat funds distributed in the form of business capital, training, and mentoring. This has brought significant benefits, such as increasing mustahik's income through profitable businesses, creating new jobs that reduce unemployment, increasing mustahik's skills and knowledge in managing businesses, increasing mustahik's self-confidence and independence by having their own income, and strengthening social solidarity among Muslims by helping mustahik escape poverty. With its various benefits, productive zakat is a solution for the economic empowerment of mustahik.